Action competence and waste management: a case study of learner agency in two Grahamstown eco-schools,Probing the development of action competence amongst learners participating in school waste management activities : a case of two Grahamstown schools - Chiphwanya, Nellie Chimwemwe (Rhodes University, Faculty of Education, Department of Education, 2011)
There has been a growing need in environmental education to develop students' ability and will to take part in democratic processes that enable them take environmental action in their local environment. This study examined learner action competence in waste management practices in two primary school contexts in the Eastern Cape, South Africa. An interpretive case study design is used to probe how learner participation in Eco-School waste management practices enabled the acquisition of knowledge in purposeful learning and action experiences that developed the vision and agency of informed action. The research was centred on two guiding questions: 1. How informed, purposeful and action-orientated is learner participation in Eco-School waste management activities? 2. What Eco-School waste management activities are fostering active participation towards a learner-led agency? Educators in the two schools were interviewed and Eco-School portfolios were examined for evidence of the learning activities and learner achievement. This provided the contextual data for reviewing focus group interviews to probe what was significant to learners, what they came to know and how they had contributed to the process of developing better waste management in the Eco-School context. The evidence generated in the study was used to identify the roles of the various players, the significant activities and processes that enabled and constrained the emergence of learner-led agency. The main findings in the study were that teacher intentionality and school management ethos were significant in engaging learners in meaningful waste management activities in both cases. The study also revealed that although most of the waste management activities in both cases were teacher-initiated, there were spaces open for learner initiatives. However, it appeared that the activity based waste management practices mostly allowed learners to learn how to do waste management more than allowing them to find out more about the scope and nature of ii the problem of waste. This then resulted in learners talking more about what they were doing with waste than talking about what they knew about waste. There were differences in the way in which learners approached waste in the two cases. In the one case, Kingswood Junior School learners used waste artistically and carried out activities that allowed for better use of waste resources like paper while in the other School, Grahamstown SDA School, learners approached waste as a resource for making money. However, in both cases, learners appeared to enjoy the positive experiences of doing things that contributed to a cleaner environment and were of benefit to others and this gave them a sense of pride to share their experiences with others. This study was significant as it allowed me to probe learner participation and examine the development of their action competence through listening to the voices of the learners themselves and understanding what was important to them about the knowledge they gained and their vision of better waste management.
Keywords: Environmental education -- South Africa -- Grahamstown -- Case studies; Environmental education -- Study and teaching (Primary) -- South Africa -- Grahamstown -- Case studies; Student-centered learning -- South Africa -- Grahamstown -- Case studies; Refuse and refuse disposal -- Environmental aspects -- South Africa -- Grahamstown -- Case studies; Recycling (Waste, etc) -- South Africa -- Grahamstown -- Case studies; Active learning -- South Africa -- Grahamstown -- Case studies; Competency based education -- South Africa -- Grahamstown -- Case studies